2010
DOI: 10.1007/s11999-009-0818-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Grading System for Fatty Degeneration of Rotator Cuff Muscles

Abstract: Fatty degeneration of the rotator cuff muscles is considered one of the most important factors for the outcomes of cuff repair. However, the reliability of the grading system is not well validated. Two specialists in musculoskeletal radiology and three shoulder fellowshiptrained orthopaedic surgeons reviewed the fatty degeneration grades of each cuff muscle of consecutive 75 fullthickness cuff tears. Fatty degeneration grades were assessed according to the systems of Goutallier et al. and Fuchs et al. using pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 25 publications
5
99
5
Order By: Relevance
“…All MR and CTA images were evaluated again for FD and postoperative cuff integrity by an orthopaedic surgeon (JPY), for analysis of interobserver reliability. Intraclass correlation coefficients (ICC) for FD showed similar results of reliability (SSP = 0.75, 95% confidence interval [CI] = 0.66-0.81; ISP = 0.73, 95% CI = 0.66-0.78; SSC = 0.65, 95% CI = 0.56-0.72) compared with results in a previous study [13]. The ICC for postoperative cuff integrity was excellent (0.82, 95% CI = 0.75-0.89).…”
Section: Methodssupporting
confidence: 68%
“…All MR and CTA images were evaluated again for FD and postoperative cuff integrity by an orthopaedic surgeon (JPY), for analysis of interobserver reliability. Intraclass correlation coefficients (ICC) for FD showed similar results of reliability (SSP = 0.75, 95% confidence interval [CI] = 0.66-0.81; ISP = 0.73, 95% CI = 0.66-0.78; SSC = 0.65, 95% CI = 0.56-0.72) compared with results in a previous study [13]. The ICC for postoperative cuff integrity was excellent (0.82, 95% CI = 0.75-0.89).…”
Section: Methodssupporting
confidence: 68%
“…The superior and inferior parts of the subscapularis and infraspinatus muscles were evaluated separately and a mean was calculated like with the CT method. A similar method using MR arthrography was reported in another study using an oblique sagittal T1-weighted image selected at the level of the coracoid base [27]. More recently, Schiefer et al [29] reported high intraobserver and interobserver agreement when investigators had full access to the examinations without specifying a definitive plane or image.…”
Section: Classificationmentioning
confidence: 85%
“…The surgeons showed higher intraobserver agreement and interobserver agreement compared with radiologists. However, other studies have shown only moderate or poor intraobserver agreement (Table 2) [22,27,31,32]. The reasons for the high variation among studies reporting reliability of this scale are unclear, but differences in methodology and specificity of which sequences and sections were used for grading may have played a role.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Another study compared interpretation of 75 CT arthrography and MRI arthrography images by 2 radiologists and 3 fellowship-trained orthopedic surgeons (20). A higher correlation coefficient was reported for MRI arthrography…”
Section: Imaging Of Fatty Changesmentioning
confidence: 99%